Economic challenges to make South Asia free from poverty and deprivation - South Asia Economics Students Meet 2008 : Delhi, India); Meeta Kumar; Pandey, Mihir (New Delhi : Academic Foundation, 2010)
Papers presented at the fifth South Asia Economics Students Meet held at Delhi in March 2008.
Includes statistical tables.
Includes bibliographical references.
Keywords: Economic development -- South Asia -- Congresses; Infrastructure (Economics) -- South Asia -- Congresses; Rural development -- Government policy -- South Asia -- Congresses; South Asia -- Economic policy -- Congresses; South Asia -- Social policy -- Congresses